A versenyképesség növelésének lehetőségei a magyarországi vállalkozásoknál - Székely, Csaba (Közép-Európai Közlemények, 2010)
International competitiveness of Hungary has been dropped back seriously in the recent years which is caused apart from macro-economic and economic-political effects by corporate management issues as well. In general there are missing corporate strategies that could to long-lasting competitive advantages. Hungarian small and medium enterprises can recover from current economic crises only if they develop proper competitive strategies based on the theory of the strategy development and on their opportunities and competences. They should choose among the theoretically possible alternative strategies taking into consideration features of their business, markets, competitors and macro-economical environment equally. This study examines competitive strategy alternatives that are available for Hungarian small and medium enterprises and suggests focusing on some important strategic opportunities.